(3EjVGM GdeSGdc Edi bhGYO GdEeGe eGdcs - (3CHh GdYHGS CMeO Hf jMji Hf eMeO Hf YHO GdhGMO Hf Ydj GdhfTQjSj,J (B914 (3g` s ((3ehQjJGfjG s)
(3ChdgG (B:s
(3fGbU hChd GdehLhO efg hYcS gPg GdbGYOI bGYOI GdehLhO TQYkG gd gh cGdehLhO MbjbI Ce dG s
(3BNQgG (B:s
(3gPI fgGjI eeG Edjg bUOJ hHg YOJ hEjGg CQOJ s
(3GdfSNI HgG MhGTs
(3HgG JQeje hbO VGYJ HYV cdeGJgGs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B269s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B209s
Keywords: (3Gdabg GdeGdcjs